THE REALIZATIONS OF RESPONSES TO APOLOGY PERFORMED BY INDONESIANS WHO SPEAK ENGLISH AS A FOREIGN LANGUAGE (A Case Study on the Ninth Semester Students of the English Department at Indonesia University of Education) - Diana Nuraida, - (2005)
The present research investigates the Realizations of Responses to Apolog} Performed by Indonesians who Speak English as a Foreign Language. AsBrown and Levinson (1987) states that the act of apologizing isface-saving for the hearer (H) and face-threatening for the speaker (S). An apology can often he the first step to gain better understanding in a damaged relationship, so the apologizer is expected to choose the right word to utter what he/she wants to speak. How the respondents respond the apology, whether it is sincere/insincere apology, may determine the future of the relationship. The respondents of the present study were 20 students of English Department at Indonesia University ofEducation. The data were collected through discourse Completion Test (DCT). The collected data were then analyzed by using the framework proposed by Blum-Kulka (1989) and Searie (1969). The investigation revealed that the respondents respond the apology differently. It is found that the responses can be categorized an acceptance, conditional acceptance, request, minimizing, thanking, rejection, and passive comment. The categories of request is manifested in five strategies, while the categories of acceptance, conditional acceptance, minimizing, thanking, rejection, and passive comment are not further divided into finer categories because they only consists of IFIDs. Furthermore, the respondents consider the social variables, setting, the seriousness of mistake, and the initiations (the strategy of apology). While, the power is not a strong influencing factor in the realizations of responses to apology. This research concludes that an act of responses to apology cannot be separated from the speaker's attempt to observe the notion of politeness.